2001
DOI: 10.1038/sj.ijo.0801732
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine oxidase inhibition is unlikely to be relevant to the risks associated with phentermine and fenfluramine: a comparison with their abilities to evoke monoamine release

Abstract: OBJECTIVE AND DESIGN:It has been proposed that the anti-obesity agent, phentermine, may act in part via inhibition of monoamine oxidase (MAO). The ability of phentermine to inhibit both MAO A and MAO B in vitro has been examined along with that of the fenfluramine isomers, a range of selective serotonin reuptake inhibitors and sibutramine and its active metabolites. RESULTS: In rat brain, harmaline and lazabemide showed potent and selective inhibition of MAO A and MAO B , their respective target enzymes, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…Inhibition of MAO produces measurable decreases in plasma 5-HIAA. Several types of evidence obtained in rat nervous tissue suggest that phentermine and fenfluramine do not affect MAO (Baumann et al, 2000;Kilpatrick et al, 2001), and the present data confirm that high i.v. doses of these drugs do not affect plasma 5-HIAA (see Fig.…”
Section: Discussionsupporting
confidence: 80%
“…Inhibition of MAO produces measurable decreases in plasma 5-HIAA. Several types of evidence obtained in rat nervous tissue suggest that phentermine and fenfluramine do not affect MAO (Baumann et al, 2000;Kilpatrick et al, 2001), and the present data confirm that high i.v. doses of these drugs do not affect plasma 5-HIAA (see Fig.…”
Section: Discussionsupporting
confidence: 80%
“…Ulus et al (2000) suggested that phentermine and other amphetamine-type stimulants might block MAO activity in vivo. While several lines of evidence obtained in rats suggest that this is not the case (Baumann et al, 2000;Kilpatrick et al, 2001), the present study afforded a valuable opportunity to test the hypothesis that pharmacological doses of phentermine and related stimulants block MAO in nonhuman primates. As reported in Figure 5, (þ)-amphetamine, phentermine, and (6)-ephedrine failed to reduce the levels of acid metabolites of DA and 5-HT, namely, DOPAC and 5-HIAA, respectively.…”
Section: Discussionmentioning
confidence: 88%
“…In any event, phentermine has already been shown to be essentially inactive as a 5HT uptake inhibitor in vitro 14,17 (IC 50 ¼ 11 -14 mM). As for alternative mechanisms, although inhibition of monoamine oxidase (MAO) can yield relatively rapid elevations of extracellular 5HT, 18 these are usually persistent and can continue to rise for up to 5 h. 18,19 Again, however, phentermine has been shown to be extremely weak as an inhibitor of MAO A (IC 50 ¼ 100 -200 mM) 20,21 or MAO B (IC 50 ¼ 300 -900 mM). 20,21 Thus, the route by which phentermine evokes increases in extracellular 5HT in vivo is unclear.…”
Section: Discussionmentioning
confidence: 99%